Inactivation of Single Strains of Listeria monocytogenes and Salmonella Typhimurium Planktonic Cells Biofilms With Plasma Activated Liquids - Smet, Cindy; Govaert, Marlies; Kyrylenko, Alina; Easdani, Md.; Walsh, James L.; Van Impe, Jan F. (Frontiers in Microbiology, 2019)
Recent research has proven the ability of cold atmospheric plasma (CAP) for assuring food safety. A more flexible and transportable alternative is the use of plasma activated liquids (PAL), which are also known to have antimicrobial properties. However, within the context of food safety, little is known on its potential regarding decontamination. This research therefore focusses on identifying the impact of (i) the microbial species and its cell type (planktonic cells or biofilms), (ii) the CAP settings (i.e., gas composition and generation time) and (iii) PAL related factors (treatment time and PAL age) on the technologies efficacy. Cell densities were monitored using the plate counting technique for which the results were analyzed by means of predictive inactivation models. Moreover, the pH and the concentrations of long-lived species (i.e., hydrogen peroxide, nitrite, and nitrate) were measured to characterize the PAL solutions. The results indicated that although the type of pathogen impacted the efficacy of the treatment, mainly the cell mode had an important effect. The presence of oxygen in the operating gas ensured the generation of PAL solutions with a higher antimicrobial activity. Moreover, to ensure a good microbial inactivation, PAL generation times needed to be sufficiently long. Both CAP related factors resulted in a higher amount of long-lived species, enhancing the inactivation. For 30 min. PAL generation using O2, this resulted in log reductions up to 3.9 for biofilms or 5.8 for planktonic cells. However, loss of the PAL activity for stored solutions, together with the frequent appearance of a tailing phase in the inactivation kinetics, hinted at the importance of the short-lived species generated. Different factors, related to (i) the pathogen and its cell mode, (ii) the CAP settings and (iii) PAL related factors, proved to impact the antimicrobial efficacy of the solutions and should be considered with respect to future applications of the PAL technology.